Sigmoid Colon Migration of an Intrauterine Device - Funda Akpinar; Esra Nur Ozgur; Saynur Yilmaz; Oguzhan Ustaoglu (Case Reports in Obstetrics and Gynecology)
Background. Intrauterine devices (IUD) are commonly used birth control methods. Colonic perforation is an infrequent but serious complication of IUD. Case. A 34-year-old woman with 2-years history of IUD, inserted at early puerperal period, presented to gynecologist with chronic pelvic pain and dyspareunia. Radiological assessment revealed that there were two copper-T devices: one in uterine cavity and another in the colonic lumen. Attempts of retrieval with colonoscopy and laparoscopy were unsuccessful. Intrauterine device embedded in sigmoid colon wall was removed with resection of the involved segment and primary anastomosis was performed. Conclusion. Although there are cases in literature that are successfully managed with colonoscopy, in chronic cases, formation of granulation tissue complicates retrieval of an IUD by this intervention.